Tenofovir alafenamide use in pregnant and lactating women living with HIV. (2nd April 2020) - Eke, Ahizechukwu C.; Brooks, Kristina M.; Gebreyohannes, Rahel D.; Sheffield, Jeanne S.; Dooley, Kelly E.; Mirochnick, Mark
ABSTRACT: Introduction : Tenofovir alafenamide (TAF)-containing fixed-dose drug combinations (FDCs) are increasingly being used in managing pregnant women living with HIV. However, TAF is not currently recommended during pregnancy due to limited pharmacokinetic and safety data. TAF, a newer nucleotide phosphonamidate prodrug of tenofovir (TFV), achieves high levels of tenofovir-diphosphate in lymphoid cells and hepatocytes, and 90% lower systemic concentrations of TFV compared to tenofovir disoproxil fumarate (TDF), thereby maximizing TAF's antiviral efficacy, potency and clinical safety. Areas covered : This review discusses the currently available information on the pharmacology of TAF in pregnant women living with HIV. Pharmacokinetic studies with TAF during pregnancy have yielded varying results compared to postpartum, but TAF exposures during pregnancy have been within the range of those typically observed in non-pregnant adults. The efficacy and safety of TAF in treatment-naïve pregnant women living with HIV is currently being evaluated in the VESTED study, a phase-III NIH randomized clinical trial. Expert opinion : Initial pregnancy data suggest that TAF-based FDCs have high efficacy and low risk of adverse effects during pregnancy. TAF is likely to become part of first-line regimens for use in pregnant women living with HIV once additional pregnancy data from phase III trials are available.